The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00784-023-05060-9
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative 10-year performance of endodontically treated teeth with prosthetic restorations of base metal alloy double crowns with friction pins—a retrospective study

Abstract: Objectives This 120-month follow-up study aimed to investigate the complication rate of abutment teeth after endodontic pretreatment with base metal alloy double crowns with friction pins. Materials and methods A total of 158 participants (n = 71, 44.9% women) aged 62.5 ± 12.7 years with 182 prostheses on 520 abutment teeth (n = 459, 88.3% vital) were retrospectively analyzed between 2006 and 2022. Of the endodontically treated abutment teeth, 6.9% (n = 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In a recent study, 14% of the double crown's abutment was reported to have fractured during the observation period, and only a small number of them are salvageable [33]. However, another report showed no abutment loss in 84% of the study population after five years [32].…”
Section: Double Crown-retained Overdenturesmentioning
confidence: 99%
“…In a recent study, 14% of the double crown's abutment was reported to have fractured during the observation period, and only a small number of them are salvageable [33]. However, another report showed no abutment loss in 84% of the study population after five years [32].…”
Section: Double Crown-retained Overdenturesmentioning
confidence: 99%